Liberty after freedom: a history of article 21, due process and the constitution of India - Alva, Rohan J. (Gurugram HarperCollins, 2022)
Liberty After Freedom explores the origins of what is today considered the most important fundamental right in the Indian Constitution - the right to life and personal liberty guaranteed by Article 21. This is the article which in recent years made the right to privacy as well as the decriminalization of homosexuality possible. Without a doubt, Article 21 has had the most outsized influence on the progressive development of rights in India. But the story of how this important right was birthed is deeply controversial and its passage in the Constituent Assembly divided opinion like no other feature of the Constitution. Liberty After Freedom explores the intellectual beginnings of this paramount fundamental right in an attempt to decode and unravel the controversies which raged at the time the Constitution was being crafted. Written in lucid prose and drawing extensively on the Constituent Assembly debates as well as a wide array of scholarly literature, it questions long-held beliefs and sheds new and important light on the fraught history of due process and Article 21. It is an indispensable book for the legal community and for everyone interested in the genesis of the Constitution.
Keywords: Law; Constitution & Religious Group